Attending to EFL Teacher Identity: Reflective Practice in Optimising Teacher Professional Education Program - Carla Sih Prabandari (Indonesian Journal of English Language Studies (IJELS), 2020)
This paper offers a discussion on the interconnection between teacher professional development, teacher learning and teacher identity and how reflective practice can optimize Indonesian EFL teachers development of professional identity. This paper provides some ideas for designing reflective activities to foster the development of teacher identity. It presents practical suggestions about how to incorporate reflections in learning activities during the Teacher Professional Education (TPE). The reflection model proposed by Kolb (2015) is preferred as it is considered to be simpler and more suitable in the context of TPE in Indonesia. The reflective practice during TPE is fundamental to promote lifelong teacher learner identity.